2020
DOI: 10.1038/s41467-020-15910-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of the nuclear membrane protein Emerin in front-rear polarity of the nucleus

Abstract: Cell polarity refers to the intrinsic asymmetry of cells, including the orientation of the cytoskeleton. It affects cell shape and structure as well as the distribution of proteins and organelles. In migratory cells, front-rear polarity is essential and dictates movement direction. While the link between the cytoskeleton and nucleus is well-studied, we aim to investigate if front-rear polarity can be transmitted to the nucleus. We show that the knock-down of emerin, an integral protein of the nuclear envelope,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…Therefore, rearrangement of the cytoskeleton through mechanotransductive machinery leads to changes in the nucleus polarity and positioning within the cell, influencing cell migration (Vassaux et al, 2019;Moure and Gomez, 2020). Indeed, both F-actin and focal adhesion distributions were strongly influenced by this repositioning of nuclear compartment (Nastały et al, 2020). These findings provide intriguing insights that physical reorganization of the intracellular structural components and mechanotransductive players, which can be induced by changes in the tissue morphology, can directly affect FMT.…”
Section: Mechanotransduction Leads To Distinct Internal Cellular Rearmentioning
confidence: 91%
See 3 more Smart Citations
“…Therefore, rearrangement of the cytoskeleton through mechanotransductive machinery leads to changes in the nucleus polarity and positioning within the cell, influencing cell migration (Vassaux et al, 2019;Moure and Gomez, 2020). Indeed, both F-actin and focal adhesion distributions were strongly influenced by this repositioning of nuclear compartment (Nastały et al, 2020). These findings provide intriguing insights that physical reorganization of the intracellular structural components and mechanotransductive players, which can be induced by changes in the tissue morphology, can directly affect FMT.…”
Section: Mechanotransduction Leads To Distinct Internal Cellular Rearmentioning
confidence: 91%
“…Depending on the abundance of its components, the ECM can present different microarchitectures, leading to different mechanical and physical properties. Importantly, interactions between the cells and the different ECM components can directly regulate cell behavior such as migration and development (Park et al, 2018;Changede et al, 2019;Nastały et al, 2020).…”
Section: Ecm Composition Regulates Fibroblast Mechanosensingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported to be enriched at the ONM under cyclic strain stress ( Le et al, 2016 ), whereas Emerin-deficient cells showed impaired expression of mechanosensitive genes in response to strain ( Lammerding et al, 2005 ). Emerin has also been recently shown to be associated with nuclear stiffening and to be involved in maintaining nuclear front–rear polarity ( Nastały et al, 2020 ). Mutations in Emerin-encoding gene ( EMD ) cause X-linked EDMD that is associated with progressive muscle wasting and weakness followed by cardiac disease with conduction defects and arrhythmias ( Helbling-Leclerc et al, 2002 ).…”
Section: Nuclear Structure Components and Their Role In Mechanosensinmentioning
confidence: 99%